Modeling of Soil Nailing Configuration towards the Slope Height Due to the Land Sliding Safety - Syazili, Muhammad; Bisri, Mohammad; Andawayanti , Ussy; Hendrawan, Andre Primantyo (Journal of Ecohumanism, 2025)
This research intends to investigate the effective height for installing the soil nailing in the vertical direction of slope height. One of the effective retaining wall methods and much be used in Indonesia is by using soil nailing. The methodology consists of the usage of finite element by using the Plaxis software. The variable that is researched is the effective height of soil nailing which the configuration model of vertical direction follows the simulation. The research is conducted on 5 models as follows: the effective height of nailing is the same as slope height (Ha); then the effective height of nailing is the same as ¾ Hn; 2/3 Hn; ½ H; 1/3 H; and ¼ H. Based on the numerical simulation, the result shows that the effective height of soil nailing configuration in the vertical direction is 1/3 of slope height. The simulation result is effective enough to produce the safety value (SF) is 1.62 (> 1.5) and giving the lowest deformation value as follows: δ = 0.02318 m (< 0.005 H = 0.09 m). The research result is hoped can give a recommendation to the determination of effective height in design of soil nailing for retaining wall.